A case for a pan-Indian Ocean information grid for improved maritime domain awareness. Issue 3 (2nd September 2017) - Upadhyaya, Shishir
ABSTRACT: The Indian Ocean region, in recent years, has witnessed a proliferation of information centers which have emerged in response to various sub-regional requirements and sometimes representing diverse interest groups. This paper highlights the gaps in regional maritime domain awareness (MDA) and argues that the multiple disparate information systems have not contributed to improving overall maritime safety and security in the Indian Ocean region. It puts forward a case for a pan-Indian Ocean information grid that could integrate the various information sources to provide comprehensive MDA for the region.